Synthetic inhibitors of group IVA and group VIA phospholipase A2 - Magrioti, V.; Kokotos, G. (Anti-Inflammatory and Anti-Allergy Agents in Medicinal Chemistry, 2006)
PLA2 is an important signaling enzyme that generates multiple downstream effectors, such as arachidonic acid and PAF, which are key mediators of inflammation as well as other pathophysiological conditions. Inhibition of PLA2 is potentially an effective therapy for several inflammatory diseases. In this review, we discuss the various classes of synthetic inhibitors of Group IVA and Group VIA phospholipase A2.